УНІВЕРСАЛЬНИЙ ТРИФАЗНИЙ ПАСИВНИЙ ФІЛЬТР ГАРМОНІК СТРУМУ МЕРЕЖІ - Губаревич, В.М.; Маруня, Ю.В.; Кабан, В.П.; Матвєєв, В.Ю. (Інститут електродинаміки Національної академії наук України, 2023)
An analysis of well-known universal filters of current harmonics was carried out. A variant of the three-phase passive filter of network current harmonics is proposed, due to the change in its structure, the value of the voltage on the load is limited in operating modes close to idling. Mathematical modeling of such a system, which feeds a bridge rectifier with a capacitive filter and an active load with a power of 5 kW, was performed. The load characteristics and the dependence of the current harmonic coefficient on the change in the load power of the developed filter are given. Ref. 2, fig. 3.